The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1542/hpeds.2016-0211
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Therapy During Acute Bronchiolitis in Patients Who Later Develop Asthma

Abstract: Corticosteroids were not associated with improved outcome in patients with bronchiolitis who were later hospitalized with asthma. Moderately ill patients with no comorbidities may warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Despite its high prevalence, there are no effective therapies for bronchiolitis . Corticosteroids are often administered despite lack of efficacy in meta‐analyses, possibly influenced by clinicians’ belief that the particular patient may have a predilection towards asthma . The ability for clinicians to identify a corticosteroid‐responsive subset of bronchiolitis patients is supported by one randomized trial in which corticosteroids reduced hospital length of stay in children with eczema or familial asthma, but other studies do not show benefits in similar sub‐populations .…”
Section: Introductionmentioning
confidence: 99%
“…Despite its high prevalence, there are no effective therapies for bronchiolitis . Corticosteroids are often administered despite lack of efficacy in meta‐analyses, possibly influenced by clinicians’ belief that the particular patient may have a predilection towards asthma . The ability for clinicians to identify a corticosteroid‐responsive subset of bronchiolitis patients is supported by one randomized trial in which corticosteroids reduced hospital length of stay in children with eczema or familial asthma, but other studies do not show benefits in similar sub‐populations .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple previous studies and reviews have conflicting results of the benefit of steroids in bronchiolitis. [18][19][20][21] Cochrane systematic review and multiple guidelines have concluded that glucocorticoids do not improve clinical respiratory scores, hospitalisations rates or LOS, and do not recommend use of glucocorticoids or salbutamol in bronchiolitis. 5,7,8,22,23 In our audit, whilst <1% of infants in-hospital received glucocorticoids, clinicians in the prehospital settings administered the majority of steroids.…”
Section: Discussionmentioning
confidence: 99%
“…Principal diagnosis of bronchiolitis from ED was searched using the ED Information System (EDIS, Version 9.46.1001 ER15, HAS Solutions Pty Limited, Australia) with diagnostic codes of bronchiolitis (ICD10 codes: J21.0, J21.1, J21.8, J21.9 or ICD9 code: 466. 19). Principal diagnosis of bronchiolitis from the inpatient ward was confirmed on patient's discharge summary and/or inpatient notes.…”
Section: Methodsmentioning
confidence: 99%
“…Both treatments do not prevent hospital admission and do not improve short-and long-term outcomes in patients with bronchiolitis or the length of hospital stay. Changes in timing, dosage or duration of treatment do not influence the effects of nebulized and systemic steroids [1,20,95,[99][100][101][102][103][104].…”
Section: Nebulized Adrenalinementioning
confidence: 99%